2017
DOI: 10.17265/2159-5542/2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Is Perceived Stress of French University Students Related to Personality Traits?

Abstract: Introduction and goal: Whilst considering attending university as a potentially stressful situation, and in order to highlight predictors of stress in students, our goal is to assess the link between perceived stress and personality traits in this population. Methodology: We used, via online questionnaires, the perceived stress scale (PSS 10) and the French Big Five Inventory (BFI-Fr). The population consists of French university students (n = 483, Average age = 20.23, σ = 1.99). Results: The results show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Consequently, they face different stressful situations due to the challenging developmental tasks of the young adulthood stage which can limit their psychological comfort. According to the previous research, university life can be considered as a potentially stressful situation and college students display high levels of psychological distress, such as depression, anxiety, and specially stress (Saleh et al, 2017b). Some studies have found that the tendency to experience unpleasant emotions and suffer from low self-esteem, little optimism and a low sense of self-efficacy could be stress predictors in college students (Saleh et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, they face different stressful situations due to the challenging developmental tasks of the young adulthood stage which can limit their psychological comfort. According to the previous research, university life can be considered as a potentially stressful situation and college students display high levels of psychological distress, such as depression, anxiety, and specially stress (Saleh et al, 2017b). Some studies have found that the tendency to experience unpleasant emotions and suffer from low self-esteem, little optimism and a low sense of self-efficacy could be stress predictors in college students (Saleh et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…Everyone has distinctive traits along the primary axes of their psychological makeup, which aid in the development of distinctive patterns of behavior. Many people and students all across the world have been surveyed in a variety of global surveys to assess personality, mental health issues and stress levels (17)(18)(19) . Several worldwide research with university students revealed that a few personality traits are related to an increased chance of experiencing mental health issues as well as stress (20,21) .…”
Section: Introductionmentioning
confidence: 99%